Mini Fan With Temperature Sensor (T-FAN) / Raja Mohamad Shafiq Raja Othman - Raja Othman, Raja Mohamad Shafiq (2020)
T-Fan company is an electrical fan company with new updated or upgraded technologies of fan itself. It is well-known as a direct seller of the fan with the latest technologies across the state. New updated fan technology was fan upgraded with the temperature sensor have been T-Fan company mainstay. T-Fan company was founded in January 2020, to sell fan products. T-Fan has plants that manufacture its products located in Perak. Location of the company is located on the outskirt of Ipoh, Perak which is near the manufacturing factory and raw materials suppliers of product. T-Fan company is encompassing a range of premium innovative products that marketed through an independent direct-selling force. These include innovative technologies that implement in our product. Today, T-Fan Company continues to break new grounds as an attractive and rewarding business opportunity. It strives to make a difference in the communities in which it operates, by offering them the opportunity to create friendlier environment products for where everyone can participate.